Proceedings of the 2nd International Conference on Electronic and Mechanical Engineering and Information Technology (2012) 2012
DOI: 10.2991/emeit.2012.342
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tempering temperature on microstructures and properties of niobium and titanium microalloying low carbon bainite steel

Abstract: Abstract. The effect of tempering temperature on microstructures and mechanical properties of niobium and titanium microalloying low carbon bainite steel was investigated. The results indicate that the mechanical properties change is mainly controlled by the structure evolution, and as the structure evolution during tempering is complex, the mechanical properties do not monotonously increase or decrease with the increasing of tempering temperature. IntroductionHight strength low carbon bainite steel is a new d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Recently, Huang et al (2013) have shown, through Charpy impact test, that the reduced activation ferritic martensitic steel (similar to the material examined in the current work), with M 23 C 6 coarsened by heat treatment, has less absorbed energy than the material with no such coarsening. The absorbed energy in Charpy impact tests for low carbon bainite steels with different tempering temperatures has been shown to have almost positive correlation with ductility (tensile elongation) by Li et al (2012). Therefore, the result of Huang et al (2013) implies that the coarsening M 23 C 6 reduces material ductility.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, Huang et al (2013) have shown, through Charpy impact test, that the reduced activation ferritic martensitic steel (similar to the material examined in the current work), with M 23 C 6 coarsened by heat treatment, has less absorbed energy than the material with no such coarsening. The absorbed energy in Charpy impact tests for low carbon bainite steels with different tempering temperatures has been shown to have almost positive correlation with ductility (tensile elongation) by Li et al (2012). Therefore, the result of Huang et al (2013) implies that the coarsening M 23 C 6 reduces material ductility.…”
Section: Discussionmentioning
confidence: 97%